The Lion of Piraeus: Democracy and Denmark - Forsén, Björn (Classica et Mediaevalia, 2026)
This article addresses where the lion of Piraeus originally stood as well as the date and reason for its erection, why and when it was moved to the harbour shore of Piraeus and rebuilt as a fountain, as well as how during the nineteenth century it was exploited as a source of inspiration for modern lion sculptures. It is argued that the lion originally was erected outside the Eetioneian gate during the last years of the 390s or the 380s to honour those who had given their lives in the battle(s) of Mounychia and/or Piraeus in 404/403 BC to enable the re-establishment of the democratic government in Athens.